Effect of lattice expansion degree on properties and electromagnetic field response of InSe, GaSe and clathrates on their basis - Іващишин, Федір Олегович; Григорчак, Іван Іванович; Гордіюк, Тетяна Миколаївна; Швець, Роман Ярославович; Кулик, Юрій Орестович (Eastern-European Journal of Enterprise Technologies, 2015)
The effect of the expansion degree of the crystal lattice of layered semiconductors GaSe and InSe on their properties and behavior in a constant magnetic field and under light is investigated. It is revealed that changes in the crystallographic parameters, as well as in the parameters of the energy spectrum of the defects that determine their kinetic and polarization properties at room temperature are not monotonic functions of the expansion degree. It is found that changes in response to the magnetic field and the light wave field have the same nature. As an example, the changes in the structure and physical properties of InSe<CS(NH2)2> clathrates for the 2- and 4-fold expansion, synthesized under different conditions are examined. Thus, the synthesis of these clathrates in a magnetic field leads to the appearance of positive and negative magnetoresistance for the 2- and 4-fold lattice expansion respectively. Opposite effects may be caused by asymmetry inversion of the density of states above and below the Fermi level depending on the expansion degree of the single crystal lattice.